Annealing temperature induced physical characteristics of CuO films grown by magnetron sputtering. (15th August 2021) - Peng, Wenbo; Zhou, Yijian; Li, Jingjie; Liu, Yue; Zhang, Jiahui; Xiang, Guojiao; Zhu, Xuefeng; Li, Rong; Wang, Hui; Zhao, Yang
Abstract: CuO films are expected to be an attractive photovoltaic material in the field of optoelectronic device. However, the applications of these films have been limited due to the difficulty in controlling the crystalline quality and conductivity as a result of the undesirable sensitivity to growth conditions. Herein, we report the preparation of CuO films by the radio frequency (RF) magnetron sputtering and then the as-grown films were annealed by the thermal annealing furnace under the annealing temperatures of 300, 500, 700 and 900 °C, respectively. The crystal structures, surface morphology, optical and electrical properties of CuO films were systematically investigated. The X-ray diffraction results revealed that the intensity of CuO (002) diffraction was significantly enhanced while the crystalline orientation was unchanged after annealing. Moreover, the crystal size, interplanar spacing and inhomogeneous strain were also determined. From the image of scanning electron microscope, the surface morphology of CuO films exhibited a transition from pyramid to oval shape with the increase of annealing temperature. The absorption measurement showed the band gap of prepared CuO films varied from 1.485 to 1.631 eV. Moreover, Hall effect indicated the mobility and carrier concentration of the CuO films could be adjusted from 0.026 to 0.316 cm 2 /v·s and 4.15 × 10 18 to 9.23 × 10 19 cm -3, respectively. Highlights: CuO films prepared by magnetron sputtering were annealed at different temperatures. The crystal size, interplanar spacing and inhomogeneous strain were determined. The crystal orientation was determined by texture coefficient and standard deviation. The surface morphology exhibited a transition from pyramid to oval shape. Annealing treatment could improve the crystallization quality of CuO films.